Determinants of farmers, perception towards forest conservation in western low lands of Ethiopia. Issue 3 (3rd April 2022) - Melak, Degsew; Dagnew, Abebe; Yehuala, Sisay; Gelaw, Adugna
ABSTRACT: This study was conducted in North Western Ethiopia to identify key factors that explain farmers' perception towards forest conservation using primary data, collected from 135 respondents. Descriptive statistics, factor analysis, and regression analysis techniques were used to analyse the data. The findings of the study revealed that education level was positively correlated with low perception of farmers towards conservation of forest at the 5% level of significance. Land size had a negatively explained low perception of farmers towards conservation of forests. Diversity of income sources has explained forest conservation positively. Forest conservation initiatives should promote education, alternative livelihoods, and intensive land management.